Strength-Based Parenting and Well-Being in Adolescence [Strength-Based Parenting dan Kesejahteraan Remaja] - Agnes Maria Sumargi; Jessica Giovanni (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
Adolescents’ well-being deserves attention as it promotes adolescents’ general health. Parenting is a factor that may influence adolescents’ well-being. Unfortunately, some parents provide only limited support to their adolescents and show ineffective parenting. Strength-based parenting (SBP) is a parenting style where parents seek to deliberately identify and develop positive conditions, processes, and qualities in their children. Research conducted in Western culture showed that strength-based parenting (SBP) was associated with adolescents’ subjective well-being, particularly life satisfaction. This present study extends the past research by involving adolescent sample from Eastern culture (Indonesia) and including the measure that combines both subjective and psychological well-being. Particularly, this study examined if strength-based parenting (SBP; strength knowledge and strength use) predicted adolescent well-being. Participants were 191 high school students in Surabaya (15-18 years old). Participants completed the Pemberton Happiness Index (PHI) and Strength-Based Parenting Scale (SBPS). Results showed that both strength knowledge and strength use were positively related to adolescent well-being. This indicates that parents’ recognition and encouragement to use adolescents’ strengths has helped adolescents to understand their own potentials and therefore, generate positive feelings and meaningful experiences. Thus, strength-based parenting (SBP) does not only benefit adolescents from Western culture, but also adolescents from Eastern culture (Indonesia). Kesejahteraan remaja perlu mendapat perhatian karena dapat meningkatkan kesehatan remaja secara umum. Pengasuhan orangtua merupakan salah satu faktor yang mungkin mempengaruhi kesejahteraan remaja. Namun, sebagian orangtua memberikan dukungan yang terbatas kepada anak remajanya dan menerapkan pengasuhan yang kurang efektif. Strength-based parenting (SBP) merupakan gaya pengasuhan dimana orangtua secara sengaja mengidentifikasi dan mengembangkan kondisi, proses, dan kualitas positif anak. Riset yang dilakukan dalam budaya Barat menunjukkan bahwa strength-based parenting (SBP) berkorelasi dengan kesejahteraan subjektif remaja, khususnya kepuasan hidup. Penelitian ini memperluas penelitian sebelumnya dengan melibatkan sampel remaja dari budaya Timur (Indonesia) dan menggunakan alat ukur yang menggabungkan kesejahteraan subjektif dan psikologis. Secara khusus, penelitian ini bertujuan untuk menguji apakah strength-based parenting (SBP; strength knowledge dan strength use) dapat memprediksi kesejahteraan remaja. Penelitian ini melibatkan 191 orang siswa Sekolah Menengah Atas (SMA) di Surabaya (15-18 tahun). Partisipan mengisi Pemberton Happiness Index (PHI) dan Strength-Based Parenting Scale (SBPS). Hasilnya menunjukkan bahwa strength knowledge dan strength use berhubungan positif dengan kesejahteraan remaja. Hal ini menandakan bahwa pengetahuan orangtua tentang kekuatan remaja dan dorongan orangtua agar remaja menggunakannya dapat membantu remaja memahami potensi-potensinya dan karena itu, menumbuhkan perasaan positif dan pengalaman yang bermakna. Dengan demikian, strength-based parenting (SBP) tidak hanya bermanfaat bagi remaja dalam budaya Barat, tetapi juga remaja dari budaya Timur (Indonesia).